READING NATURE AS IMAGE AND A CRITICISM TOWARDS ENVIRONMENTAL PROBLEMS IN DAVE SMITHÃ¢â¬â¢S POEM, RAIN FOREST - Yulianto, Henrikus Joko (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2010)
Rapid global development brings some changes in our physical environment. Literary work as a social media need to play a role in encouraging peopleÃ¢â¬â¢s understanding and awareness of the threatened condition of our natural surroundings. Poetry as one of literary genres often depict nature as the image and poetic representation. Romantic British poetry is one tradition that remarkably delineates and glorifies the beauty of nature as their poetic manifesto. In America, there wasÃÂ transcendentalism that similarly cherished the glory of nature through the transcendentalistsÃ¢â¬â¢ works such as poetry and fiction. In contemporary American poetry, the splendor of nature again emerges as poetics in many of their works. However, different from their previous modern poetic tradition, this contemporary one put forward nature not just as image but also convey some criticisms towards environmental problems.